Low Peripheral T Follicular Helper Cells in Perinatally HIV-Infected Children Correlate With Advancing HIV Disease - McCarty, Bret; Mwamzuka, Mussa; Marshed, Fatma; Generoso, Matthew; Alvarez, Patricia; Ilmet, Tiina; Kravietz, Adam; Ahmed, Aabid; Borkowsky, William; Unutmaz, Derya; Khaitan, Alka (Frontiers in Immunology, 2018)
Background T follicular helper (Tfh) cells are crucial for B cell differentiation and antigen-specific antibody production. Dysregulation of Tfh-mediated B cell help weakens B cell responses in HIV infection. Moreover, Tfh cells in the lymph node and peripheral blood comprise a significant portion of the latent HIV reservoir. There is limited data on the effects of perinatal HIV infection on Tfh cells in children. We examined peripheral Tfh (pTfh) cell frequencies and phenotype in HIV-infected children and their associations with disease progression, immune activation, and B cell differentiation. Methods In a Kenyan cohort of 76 perinatally HIV-infected children, comprised of 43 treatment-naïve (ART−) and 33 on antiretroviral therapy (ART+), and 42 healthy controls (HIV−), we identified memory pTfh cells, T cell activation markers, and B cell differentiation states using multi-parameter flow cytometry. Soluble CD163 and intestinal fatty acid-binding protein plasma levels were quantified by ELISA. Results ART− children had reduced levels of pTfh cells compared with HIV− children that increased with antiretroviral therapy. HIV+ children had higher programmed cell death protein 1 (PD-1) expression on pTfh cells, regardless of treatment status. Low memory pTfh cells with elevated PD-1 levels correlated with advancing HIV disease status, indicated by increasing HIV viral loads and T cell and monocyte activation, and decreasing %CD4 and CD4:CD8 ratios. Antiretroviral treatment, particularly when started at younger ages, restored pTfh cell frequency and eliminated correlations with disease progression, but failed to lower PD-1 levels on pTfh cells and their associations with CD4 T cell percentages and activation. Altered B cell subsets, with decreased naïve and resting memory B cells and increased activated and tissue-like memory B cells in HIV+ children, correlated with low memory pTfh cell frequencies. Last, HIV+ children had decreased proportions of CXCR5+ CD8 T cells that associated with low %CD4 and CD4:CD8 ratios. Conclusion Low memory pTfh cell frequencies with high PD-1 expression in HIV+ children correlate with worsening disease status and an activated and differentiated B cell profile. This perturbed memory pTfh cell population may contribute to weak vaccine and HIV-specific antibody responses in HIV+ children. Restoring Tfh cell capacity may be important for novel pediatric HIV cure and vaccine strategies.